Global burden of early-onset cardiovascular disease attributable to fine particulate matter pollution from 1990 to 2021: a systematic analysis for the global burden of disease study 2021 - Yixuan Jiang; Huihuan Luo; Guangguo Fu; Jinmiao Chen; Haidong Kan; Renjie Chen (BMC Medicine)
Abstract Background Fine particulate matter (PM2.5) is linked to early-onset cardiovascular disease (CVD); however, the corresponding disease burden has not been assessed. This study aims to evaluate the global, regional, and national early-onset CVD burden attributable to PM2.5 from 1990 to 2021. Methods We calculated the number, age-standardized rate, and percentage of CVD deaths and disability-adjusted life-years (DALYs) attributable to PM2.5 among individuals aged 25–49 years from 1990 to 2021 based on the Global Burden of Disease Study 2021. Stratified analyses were performed by sex, age, disease subtype, sociodemographic index (SDI), and country. We further calculated estimated annual percentage change to assess the temporal trends. Results In 2021, the age-standardized death and DALY rates (per 100,000) of early-onset CVD attributable to total PM2.5 were 10.93 (95% confidence interval, 10.89–10.97) and 562.12 (561.84–562.39), respectively. The burden was generally higher in males, with age-standardized death and DALY rates approximately double those in females. Individuals living in regions with lower SDI faced substantially greater burden compared to those in higher-SDI regions. Those with ischemic heart disease experienced higher burden than individuals with stroke. From 1990 to 2021, the burden attributable to total and household PM2.5 declined consistently, with estimated annual percentage change in age-standardized death rates of − 1.56% (− 1.68% to − 1.45%) and − 3.22% (− 3.48% to − 2.96%), respectively. The burden from ambient PM2.5 continued to rise, and only began to decline since the last decade, with an estimated annual percentage change in age-standardized death rates of 0.37% (0.23%–0.52%). In contrast, the late-onset CVD burden decreased for both ambient and household exposures. Conclusions Despite significant reduction in early-onset CVD burden attributable to total and household PM2.5 from 1990 to 2021, the burden from ambient PM2.5 remains a persistent challenge. Males, individuals living in regions with lower SDI, and those with ischemic heart disease face a higher burden. Geographically tailored and population-specific interventions are needed to mitigate early-onset CVD burden.